Rudenica and Its Place in the Moravian Serbia Architecture - Gugolj, Branka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Built at the turn of the 14th century, as an endowment of nobleman Vukašin and his wife Vukosava, Rudenica attracted the attention of scholars of Serbian medieval architecture as early as the 19th century. The hardships of the church, as well as lack of data about its original appearance, resulted in two failed restorations. Based on historical sources, preserved and partially published archival documentation, as well as comparisons with chronologically and topographically similar monuments, the previous findings are reexamined in the paper, in order to determine its place in the development of the Moravian Serbia architecture.
Keywords: Rudenica; architecture; sculpture; painted ornamentation